Metamemória e Doença de Alzheimer - Perches, Lucas Gonçalves (Universidade Federal de São Carlos, 2021)
Alzheimer's Disease is a degenerative disease that mainly affects the cognitive function of memory and because many of the patients are unaware of their own difficulties, their ability to properly judge their mnemonic functions is considered. Metacognition is associated with understanding one's own cognitive functions, so that metamemory is the ability to know, monitor and control the mnemonic process. The objective of this work is to compare the metacognitive knowledge and monitoring, specifically in relation to metamemory, of elderly people with signs of Alzheimer's Disease (AD) and elderly people without signs of cognitive decline. Participants were divided into two groups: the first group consisted of 13 elderly people, aged between 62 and 75 years, with no indications of cognitive decline; the second group consisted of 5 elderly people diagnosed with Alzheimer's Disease at a mild level, aged between 66 and 65 years. The NEUPSILIN memory subtests and the Metacognitive Judgments Register were used, which aims at the participant to indicate the knowledge about his mnemonic ability and estimate his performance after the application of the memory subtests. Descriptive statistics, Man-Whitney test and correlational analyzes were performed involving metacognitive knowledge, performance in memory subtests and judgment of performance. The results indicated that the two groups of elderly people showed little knowledge about their own memory and the elderly with Alzheimer's tended to overestimate their performance in relation to working memory and semantic episodic verbal memory.
Metamemory and Alzheimer´s Desease
Keywords: Metamemória; Cognição; Idosos; Metamemory; Cognition; Elderly; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO